Effects of biostimulants on chlorophylls and number of leaves in pepper (Capsicum annuum L.) cultivation under semi-protected conditions - Cobena Montes, Yelitza Lilibeth (2022)
In Ecuadorian agriculture, large amounts of chemical fertilizers are used and the cultivation of peppers (Capsicum annuum L.) is no exception in that reality that causes so much damage to the environment, soils, ground and surface waters, as well as the human health. An alternative in recent decades is the use of biostimulants, which reduce the negative impacts produced by the indiscriminate use of synthetic chemical fertilizers. This research aimed to evaluate the effect of different biostimulants (bovine manure, vermicompost leachates from bovine and goat manure, efficient microorganisms) on the chlorophyll content and the number of leaves in the plants of 5 pepper hybrids (Salvador, Quetzal, Odín, Nathalie and Canario) under conditions of semi-protected cultivation and localized irrigation, in the period from 2016 to 2019. In the research with the different hybrids, the experimental design of random blocks with 3 replicates was used. The relative chlorophyll content and the number of leaves were measured 45 days after transplantation. The application of the biostimulants induced significant favorable effects in the evaluated variables and the differences were expressed depending on the hybrid, dose and type of biostimulants, observing in each hybrid that at least one of the doses of biostimulants produced values ​​similar or higher than those reached with chemical fertilization based on nitrogen, phosphorus and potassium. This shows that the use of biostimulants constitutes a beneficial option for the partial substitution of the application of chemical fertilizers in the cultivation of pepper hybrids.